(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The aim of this paper is to develop framework to generate squeezed light for binary quantum communication. Both theoretical and experimental models to generate squeezed state Â using optical parametric amplifier (OPO), which is implemented around He-Ne laser, are described in details.Â The results will be used as a guide line to investigate the performance of squeezed light-based quantum communication over noisy channel and this issue will be presented in accompanying paper [1].Â Â